С небес на землю: роман / Татьяна Устинова - Устинова Татьяна Витальевна (Первая среди лучших, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54006 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У 80 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44